Expanding the Notion of Historical Text through Historic Building Analysis - Baron, Christine; Dobbs, Christina (Journal of adolescent & adult literacy, 2015)
Among the disciplinary skills necessary for understanding in the social studies classroom is the ability to determine context and build meaning from past events. Historical buildings are an important component of historical study, and they serve as a type of nontraditional text that students can decode and use to construct meaning about multiple historical contexts. The skills used to understand and analyze historical buildings are in and of themselves important, but engaging them also builds critical deep comprehension skills as well. This paper presents a research-tested framework for historic building analysis that can be used to build disciplinary analytical skills in history, while meeting the challenges of the Common Core Standards, which require that students be able to deeply understand a variety of types of traditional and nontraditional texts.